Users’ Experiences with Web-Based Mental Health App During COVID-19 - Koushkaki, Sara Rahmanian; Banta, Jim E.; Heilemann, MarySue V.; Grohar, Albin H.; Chung, Kyusuk; Wells, Kenneth (Journal of technology in behavioral science, 2024)
The COVID-19 pandemic has had a significant impact on individuals, families, and communities, leading to increased stress, anxiety, and mental health issues. To address these needs, Together for Wellness/Juntos por Nuestro Bienestar (T4W/Juntos), a website providing mental health resources, was created. This study aims to understand the experiences of users of the T4W/Juntos website, to learn about the benefits of the website for its users during the pandemic, and to identify areas for improvement. A thematic analysis was conducted with answers given by 199 participants who responded to at least one of six open-ended questions that were included with other close-ended questions (reported elsewhere) in an electronically administered survey. The open-ended survey questions were developed with input from diverse stakeholders, including under-resourced populations. The sample was recruited through partnerships with 11 state-wide agencies. Five main themes were identified from analysis of the data. The major themes were (1) Disruptions and Challenges Experienced During the COVID-19 Pandemic, (2) Benefiting from an Accessible Website, and (3) Wanting Access to Additional Resources. The University of California, Los Angeles (UCLA), Institutional Review Board (IRB) for Human Subjects approved the study, and participants provided informed consent. The website provided access to resource links that brought needed information, a sense of empowerment, and support for individuals dealing with mental health issues related to the pandemic. Participants highly recommended the website to others. However, they also suggested improvements such as more specific resources and additional languages.